Placental syphilis: a comprehensive review of routine histomorphology, HIV co-infection, penicillin treatment, immunohistochemistry, and polymerase chain reaction. - Marais, Yolandi Anne (Stellenbosch : Stellenbosch University, 2023)
Thesis (MMed)--Stellenbosch University, 2023.